(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article presents ideas that the creation of a high exemplary spiritual and moral system, based on the requirements of high principles of the moral ideal, is a guarantee of survival from disasters similar to the current “mass culture”. The article, taking into account that strengthening the moral and aesthetic culture of youth is a pedagogical, philosophical and sociological problem, provides a philosophical understanding of the constructive relationship between the defining, governing and controlling functions of the moral ideal in the emerging moral and aesthetic culture of youth, substantiates the mutually determining factors in the formation of the internal system of moral ideal of personality.